2021
DOI: 10.1029/2020tc006283
|View full text |Cite
|
Sign up to set email alerts
|

Rifting of Collapsed Orogens: Successive Incision of Continental Crust in the Proximal Margin Offshore Norway

Abstract: Structures related to orogenic "collapse" may provide an important template for reactivation during later rifting. In the proximal rifted margin offshore Norway, the tectono-sedimentary template related to collapse of the Caledonian mountain belt became widely eroded but inherited metamorphic core complexes and detachment faults evolved further in Late Paleozoic and Earliest Mesozoic time and became associated with very significant crustal thinning. The earliest rifting mode was dominated by structures that mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 62 publications
2
39
0
Order By: Relevance
“…The Scotian margin, for instance, shows major changes in the crustal architecture and the magmatic budget during breakup, with a magma-poor segment in the north and a magma-rich segment in the south 48 . Whereas the Norwegian margin, on the other hand, appears to be affected by a strong structural segmentation from the earliest phases of extension preserved in the proximal domain 49 , 50 to segmentation along the necking and hyperextension-exhumation domains 51 . Unlike the Labrador Sea, which opened perpendicular to Precambrian terrains, these margins initiated on, and parallel to, Palaeozoic Appalachian and Caledonian terrains, respectively, with a substantially more complex structural inheritance.…”
Section: Discussionmentioning
confidence: 98%
“…The Scotian margin, for instance, shows major changes in the crustal architecture and the magmatic budget during breakup, with a magma-poor segment in the north and a magma-rich segment in the south 48 . Whereas the Norwegian margin, on the other hand, appears to be affected by a strong structural segmentation from the earliest phases of extension preserved in the proximal domain 49 , 50 to segmentation along the necking and hyperextension-exhumation domains 51 . Unlike the Labrador Sea, which opened perpendicular to Precambrian terrains, these margins initiated on, and parallel to, Palaeozoic Appalachian and Caledonian terrains, respectively, with a substantially more complex structural inheritance.…”
Section: Discussionmentioning
confidence: 98%
“…Viola et al (2011) observed that an early high-grade fabric associated with top-to-the SE compression is partly reworked by later lower-grade (greenschist facies) top-tothe-W extensional shearing. The Ørje Shear Zone has been traced southwards into the Grann zone (Hageskov, 1980), which is a local equivalent to the Dalsland boundary thrust (Berthelsen, 1980;Gorbatschev, 1988;Park et al 1991) and is accordingly regarded as a part of the Dalsland boundary thrust and the Lerdal zone system (Berthelsen, 1980;Park et al 1991). The latter is described as an imbricate stack of shear zones dipping 20-40°to the W and with a top-to-the-E displacement (Park et al 1991).…”
Section: A the Himdalen-ørje Deformation Zonementioning
confidence: 99%
“…Fig. 3 shows an earthquake cluster (Byrkjeland et al, 2000) in the area where the North Sea N-S-trending Mesozoic fault system interacts with the older, Devonian and Mesozoic, NE-SW Møre-Trøndelag Fault Complex (MTFC) system (Doré et al, 1997;Gabrielsen et al 1999;Olsen et al, 2007;NPD, 2020;Osmundsen et al, 2021), whereas the eastern branches of the MTFC are mostly aseismic at present. It is likely that this region experienced tectonic deformation during deglaciation, not least since some deformation is still ongoing (Fig.…”
Section: Storegga Megaslide and Tsunamimentioning
confidence: 99%